Endogenously produced catecholamines improve the regulatory function of TLR9-activated B cells. - Nadine Honke; Torsten Lowin; Birgit Opgenoorth; Namir Shaabani; Alexander Lautwein; John R Teijaro; Matthias Schneider; Georg Pongratz (PLoS Biology, 2022)
The sympathetic nervous system (SNS) contributes to immune balance by promoting anti-inflammatory B cells. However, whether B cells possess a self-regulating mechanism by which they modulate regulatory B cell (Breg) function is not well understood. In this study, we investigated the ability of B cells to synthesize their own catecholamines upon stimulation with different B cell activators and found that expression of the enzyme tyrosine hydroxylase (TH), required to generate catecholamines, is up-regulated by Toll-like receptor (TLR)9. This TLR9-dependent expression of TH correlated with up-regulation of adrenergic receptors (ADRs), enhanced interleukin (IL)-10 production, and overexpression of the co-inhibitory ligands programmed death ligand 1 (PD-L1) and Fas ligand (FasL). Moreover, concomitant stimulation of ß1-3-ADRs together with a B cell receptor (BCR)/TLR9 stimulus clearly enhances the anti-inflammatory potential of Bregs to suppress CD4 T cells, a crucial population in the pathogenesis of autoimmune diseases, like rheumatoid arthritis (RA). Furthermore, TH up-regulation was also demonstrated in B cells during the course of collagen-induced arthritis (CIA), a mouse model for the investigation of RA. In conclusion, our data show that B cells possess an autonomous mechanism to modulate their regulatory function in an autocrine and/or paracrine manner. These findings help to better understand the function of B cells in the regulation of autoimmune diseases and the interplay of SNS.